Sexual Laborers and Entrepreneurial Women: Articulating Collective Identity in India's HIV/AIDS Response. (4th September 2019) - Vijayakumar, Gowri
Abstract: This article uses ethnographic and interview methods to compare two groups of sex workers in Bangalore, both of which formed during the response to the HIV/AIDS epidemic. In this context, donor priorities fundamentally shaped the landscape for sex worker organizations, but the two groups formed very different collective identities. I argue that the content of collective identity is not predetermined by the conditions set by global Northern funding. Instead, I show how collective identity is articulated, in a locally specific process of relating political orientations to local associational fields, within, but not predetermined by, global funding constraints. As each group positioned itself in a distinct local associational field, it articulated a distinct collective identity, the Women's Collective as entrepreneurial women (a more respectable collective identity), and the Union as sexual laborers (a more transgressive one). Articulation unfolded through material as well as symbolic processes, shaping members' life trajectories and their understandings of them. This article complicates accounts of Northern funding and institutional opportunities as predetermining the paths and visions of social movements.